2022
DOI: 10.1002/kjm2.12528
|View full text |Cite
|
Sign up to set email alerts
|

THBS2 promotes cell migration and invasion in colorectal cancer via modulating Wnt/β‐catenin signaling pathway

Abstract: Colorectal cancer (CRC) is the most common human digestive malignancy with a poor prognosis; the pathophysiology of colon cancer involves multiple linkages of regulatory networks. Recently, thrombospondin 2 (THBS2) has been extensively studied for its role in cancer progression. In this study, we evaluated the expression of THBS2 in CRC tissues and studied the possible mechanism by which THBS2 regulates CRC progression. Our results showed that the upregulation of THBS2 in CRC tissues and CRC cell lines and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…55 THBS2 promotes CRC cells migration and invasion by regulating the Wnt/beta-catenin signalling pathway. 47 In our result, knockdown BGN or THBS2 significantly increased the proliferation inhibitory effect on CRC cells induced by 5-FU and oxaliplatin treatment. Thus, to improve the poor outcomes of CRC patients with metastasis, it may be therapeutically useful to consider ways suppress THBS2 or BGN expression in CRC and combine this with 5-FU treatment as a combination treatment strategy.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…55 THBS2 promotes CRC cells migration and invasion by regulating the Wnt/beta-catenin signalling pathway. 47 In our result, knockdown BGN or THBS2 significantly increased the proliferation inhibitory effect on CRC cells induced by 5-FU and oxaliplatin treatment. Thus, to improve the poor outcomes of CRC patients with metastasis, it may be therapeutically useful to consider ways suppress THBS2 or BGN expression in CRC and combine this with 5-FU treatment as a combination treatment strategy.…”
Section: Discussionsupporting
confidence: 57%
“…Meanwhile, BGN is overexpressed in colon cancer stem cells and activates NF‐κB pathway, which leads to chemotherapy resistance, 54 and BGN knockdown enhanced the HT‐29 cells' sensitivity to 5‐FU treatment 55 . THBS2 promotes CRC cells migration and invasion by regulating the Wnt/beta‐catenin signalling pathway 47 . In our result, knockdown BGN or THBS2 significantly increased the proliferation inhibitory effect on CRC cells induced by 5‐FU and oxaliplatin treatment.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…CRC aggressiveness is triggered by SERPINE1 activation by ARNTL2 and circadian rhythm variations in circulating PAI-1 levels 44 . CRC cells migrate and invade more rapidly when THBS2 regulates the Wnt/β-linked protein signaling pathway 45 . It has been reported that COMP promotes cell proliferation during the early stages of colon cancer tumorigenesis 46 .…”
Section: Discussionmentioning
confidence: 99%
“…58 A similar finding was observed by Qu et al that THBS2 promoted cell migration and invasion in colorectal cancer through the regulation of the Wnt/β-catenin signaling pathway. 59 In addition, THBS2 is more highly expressed in gastric cancer than in cancer-adjacent tissues. 60 Therefore, formononetin reduced the expression of all these targets, which could be one of the major regulatory mechanism of the observed decrease in the proliferation and migration of bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%